Contributors and moderators of quality of life in caregivers of Alzheimer´s disease patients - Pereira, M. Graça (2021)
Aim and objective: This study aimed to identify the variables that contributed to Quality of Life (QoL) of Alzheimer's Disease (AD) caregivers, taking into consideration the caregiving context, stressors, role strains, and resources.Methods: The sample included 102 caregivers of AD patients who answered the following instruments: Depression, Anxiety and Stress Scale-21; Satisfaction with Social Support Scale; Revised Memory and Behavioral Problems Checklist; Family Communication and Satisfaction Scales; Spiritual and Religious Attitudes in Dealing with Illness; and Quality of Life in Alzheimer's Disease - Caregiver Version.Results: Caregivers who were employed, chose the caregiving role, and received help in caring showed better QoL. Also, being younger, less caregiving daily hours, caring for patients with less memory and behavior problems, lower distress, and family satisfaction predicted better QoL. Finally, spirituality was a moderator between family communication and QoL but not between family satisfaction and QoL.Conclusion: Caregiving-context variables (age, professional status, choosing to care, receiving help in the caregiving role and duration of daily care); role strains (family dissatisfaction); stressors (caregivers' distress and patients' memory and behavioral problems); and resources (spirituality) had an impact on caregivers' QoL emphasizing the adequacy of the Stress Process Model. Intervention should also focus on spirituality given its moderating role.